Receding horizon estimation for multi‐rate sampled data systems under component‐based event‐triggered mechanisms: Handling delayed and degraded measurements - Sun, Zhenglu; Han, Chunyan; Hu, Xiaodong (IET control theory & applications, 2024)
The purpose of this article is to develop the receding horizon (RH) estimation for multi‐rate sampled systems with measurement delays and packet losses in the measurements. An event‐triggered transmission scheme is introduced to remove measurements that are unnecessary for the design of the estimator. The stochastic diagonal matrixes are introduced to represent the phenomenon of packet losses, where each component is subject to an individual Bernoulli process. The original system is firstly transformed into a delay‐free one by using the reorganized observation method. Further, a batch form and an iterative form of RH estimation are proposed by minimizing a given cost function that includes some terminal weighting terms based on the new system. The stability of the proposed RH estimation is guaranteed by the natural assumptions and a simulation instance is given to verify the effectiveness of the proposed method. This paper studied the receding horizon estimation for multi‐rate sampled system with measurement delays and packet losses. By describing the each measurement loss process as Bernoulli process, the diagonal matrix was introduced to represent the phenomenon of packet losses. Meanwhile, the component‐based event triggering mechanism was used to generate different event triggering thresholds for different channels, which effectively reduced the frequency of signal transmission.